DEVELOPMENT OF A MODULE-BASED DIGITAL LITERACY COURSE LEARNING MODEL: A NEEDS-DRIVEN APPROACH - najikhah, fatikhatun najikhah; sukardjo, Moch; Japar, M (Proceeding of International Seminar on Humanity, Education, and Language, 2025)
Rapid technological advances in the 21st century have positioned digital literacy as a fundamental competency for academic and professional success. However, educational institutions often face challenges in implementing structured, effective, and engaging digital literacy instruction. This study addresses this gap by detailing the development of a module-based learning model for a university-level digital literacy course. The study employed a Research and Development (R&D) methodology, employing Dick and Carey’s systematic model to guide the instructional design process. The initial phase involved a thorough needs assessment to identify instructional objectives and analyze learner characteristics, using a survey with 100 students and semi-structured interviews to determine core competency gaps. Findings from the needs assessment directly informed the development of performance objectives, assessment instruments, and student-centered modular learning strategies. The needs assessment results revealed significant demand for practical skills in three key areas: (1) information and data literacy, (2) collaboration and utilization of digital applications, and (3) digital content creation. The product developed was a flexible learning model consisting of ten independent learning activities with project-based assessments. Expert validation by specialists in instructional technology and curriculum design confirmed the high validity, feasibility, and relevance of the model. The study concluded that a needs assessment-driven approach is essential to creating impactful digital literacy education. The resulting module-based model provides a practical, adaptable, and validated framework for higher education institutions aiming to foster essential digital competencies.